Role of the new cytokines growth differentiation factor 15 (GDF-15) and cartilage glycoprotein 39 (YKL-40) in the development and progression of coronary artery atherosclerosis - M. V. Еzhov; T. Yu. Polevaya; Yu. G. Matchin (Klinicist, 2014)
The review presents new data of studying the nonspecific biomarkers belonging to the family of cytokines: cartilage glycoprotein 39 and growth differentiation factor 15 in coronary atherosclerosis.